Integrative taxonomy identifies Macrobiotus papei, a new tardigrade species of the Macrobiotus hufelandi complex (Eutardigrada: Macrobiotidae) from the Udzungwa Mountains National Park (Tanzania) - Stec, Daniel; Kristensen, Reinhardt Møbjerg; Michalczyk, Łukasz (Zootaxa, 2018)
In this paper we describe Macrobiotus papei, a new species of the Macrobiotus hufelandi complex from the Udzungwa Mountains National Park in Tanzania. Our research included the traditional morphology-based taxonomic analysis, supported by morphometrics, light and scanning electron microscopy imaging, as well as analysis of nucleotide sequences of three nuclear (18S rRNA, 28S rRNA, ITS-2) and one mitochondrial (COI) marker. The molecular sequences provided a more accurate description and independent verification of the taxonomic status of M. papei sp. nov. Such integrative approach requires a considerable number of individuals and eggs, which we obtained by establishing a laboratory culture of the new species. Our analyses revealed that M. papei sp. nov., by having the flexible filaments on the terminal discs of the egg processes, is most similar to Macrobiotus paulinae Stec et al., 2015 from Africa and Macrobiotus polypiformis Roszkowska et al., 2017 from South America. However, the new species can be easily distinguished from both these species by patches of cuticular granulation on the external and internal surface of legs I–III (only external patches present in in M. paulinae and M. polypiformis), two separate lateral transversal ridges with a rounded median tooth between instead of a single thin ventral transverse ridge in the third band of teeth in the oral cavity, smooth terminal discs and filaments on the egg processes (terminal discs and filaments covered by aggregations of small microgranules in M. paulinae and M. polypiformis), and by some morphometric characters of both adults and eggs.